THE HISTORY OF FIXED ASSETS REVALUATION CONDUCT IN RUSSIA: THE ACCUMULATED EXPERIENCE, RESULTS AND SURPRISES - LIDIA Kulikova (Учёт. Анализ. Аудит)
The article is devoted to the research of historical aspects of the conduct of fixed assets revaluation in Russia. The article scrutinizes the stages of the revaluation in the Russian Federation and gives the detailed characteristics of each and every stage. The prerequisites for the conduct of fixed assets revaluation are investigated in the article as well as the reasons for them and the consequences after. The specific mechanism of the conduct of each and every revaluation is studied and as a result, the problems arising during its implementation are uncovered. The results of revaluations are examined and the conclusions are made regarding the mistakes missed and some negative consequences. As a result of the revaluation dated back to 01.10.1925 the revalued objects included the fixed assets which were no longer fit for their further exploitation due to their complete depreciation and amortization. The revaluation that dates back to 01.07.1992 was held without inventory reconciliation of the fixed assets and without determining of the actual condition of each and every object. The result of the revaluation that dates back to 01.01.1994 was the formal approach to the implementation of aggregate ratios which resulted in the distortion of the information regarding the costs of fixed assets.The development tendencies of the methods of the revaluation conduct are defined in the article. Since 1996 the companies of assets valuators have been widely involved in making expert conclusions regarding the market value of the fixed assets. Since 01.01.1998 the significant peculiarity of the revaluation has been the fact that revaluation stopped being the obligation for the company, but has become its lawful right.The questions regarding the treatment of the revaluation results in accounting system are examined in the article, and the impact of these actions on the indicators of accounting reporting is studied in the article.